Bleeding with negative coagulation screening test as initial presentation of chronic myelogenous leukemia managed by fresh frozen plasma: A case report. Issue 35 (August 2019) - Wang, Yanzhi; Wang, Lina; Xi, Yaming; Li, Zijian
Abstract: Introduction: Chronic myelogenous leukemia (CML), a clonal disorder of pluripotent stem cell, rarely presents with bleeding in chronic phase due to the function preservation of the platelets. Factor (F) XIII deficiency, an extremely rare hemorrhagic disease, can cause fatal bleeding, which has been previously described in autoimmune disorders and leukemias. Patient concerns: A 38-year-old woman with a 20-day history of spontaneous subcutaneous hemorrhage visited our hospital, who presented with intracranial hemorrhage, hematuria, and delayed hematoma after a bone marrow puncture. Initial management included cytogenetics analysis, molecular analysis, and coagulation evaluation. Diagnosis: Bone marrow puncture, cytogenetics, and molecular analysis indicated the diagnosis of CML. With the normal results of clotting screening tests and platelet counting, as well as the relief of bleeding after infusion of fresh frozen plasma (FFP), acquired rare bleeding disorder probably associated with factor XIII (FXIII) deficiency. Interventions: Management with anti-hyperleukocytosis and chemotherapy, hydration, alkalization, diuresis, uric acid-lowering, molecular targeted drugs, and freshly frozen plasma transfusion therapy resolved the bleeding diathesis. Outcomes: The patient survived from the initial bleeding, however, she died. Twenty six months later due to the progression of CML. Lessons: CML can initially present as unusual bleeding, possibly related to FXIII defect. It is essential to screen coagulopathy including FXIII activity and to supplement plasma for CML patients who present initially as bleeding, which cannot be deciphered by the routine clotting screening test.